Anti‐Inflammatory Activity of a Novel Acetylene Isolated from the Roots of Angelica tenuissima Nakai. Issue 6 (27th May 2016) - Choi, Hyun Gyu; Choi, Hyukjae; Lee, Jeong‐Hyung; Min, Byung Sun; Kim, Jeong Ah
Abstract : Three polyacetylenes, one novel and two known, were isolated from the root of Angelica tenuissima . Using 1 H‐ and 13 C‐NMR, COSY, HMBC, and HMQC, their structures were found to be (3 R, 8 S )‐heptadeca‐1‐en‐4, 6‐diyne‐3, 8‐diol (1 ), falcarindiol (2 ), and oplopandiol (3 ). Absolute configurations of compound1 were established using Mosher 's esterification. In addition, the polyacetylenes (1 –3 ) were evaluated for their anti‐inflammatory activity. Compounds1 and3 showed potent inhibitory activity against lipopolysaccharide‐induced nitric oxide (NO) production in RAW267.7 macrophage cells with IC 50 values of 4.31 and 5.06 μm, respectively. Compound1 strongly inhibited inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)‐2 in a concentration‐dependent manner. Abstract :